Standar Pelayanan Angkutan Penyeberangan Tanjung Selor – Tarakan - Suryani Suryani; Imam Muazansyah (FISIP UWP, 2020)
The movement movement of the people of Tanjung Selor and Tarakan is the availability of the role of the Tanjung Selor - Tarakan crossing transportation as a driver of economic growth. It is expected that the smooth movement of passengers and goods can take place effectively and efficiently. The problem in this research is how the standard of water transportation service crossing passengers to Tanjung Selor - Tarakan in Bulungan Regency and what are the supporting factors and obstacles to the standard of water transportation service to Tanjung Selor - Tarakan. The expected results with this research. The port and the Transportation Agency of the Bulungan Regency have attempted members crossing passenger fish services as well as possible. The absence of a service SOP at the port as a standard service standard, this also makes it difficult for the Transportation Agency of the Bulungan Regency to conduct an assessment of the performance of the officers and to determine the priority of improvement. The obstacles are the lack of government officials who provide services at the port, facilities and infrastructure, weather conditions of the regional financial budget